Multi-Target Protective Effects of Gintonin in 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine-Mediated Model of Parkinson’s Disease via Lysophosphatidic Acid Receptors - Choi, Jong Hee; Jang, Minhee; Oh, Seikwan; Nah, Seung-Yeol; Cho, Ik-Hyun (Frontiers in Pharmacology, 2018)
Gintonin is a ginseng-derived lysophosphatidic acid receptor (LPAR) ligand. Although previous in vitro and in vivo studies demonstrated the therapeutic role of gintonin against Alzheimer’s disease, the neuroprotective effects of gintonin in Parkinson’s disease (PD) are still unknown. We investigated whether gintonin (50 and 100 mg/kg/day, p.o., daily for 12 days) had neuroprotective activities against neurotoxicity in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mouse model of PD. Pre-administration of 100 mg/kg gintonin displayed significantly ameliorating effects in neurological disorders (motor and welfare) as measuring using pole, rotarod, and nest building tests, and in the survival rate. These effects were associated to the reduction of the loss of tyrosine hydroxylase–positive neurons, microglial activation, activation of inflammatory mediators (interleukin-6, tumor necrosis factor, and cyclooxygenase-2), and alteration of blood-brain barrier (BBB) integrity in the substantia nigra pars compacta and/or striatum following MPTP injection. The benefits of gintonin treatment against MPTP also included the activation of the nuclear factor erythroid 2-related factor 2 pathways and the inhibition of phosphorylation of the mitogen-activated protein kinases and nuclear factor-kappa B signaling pathways. Interestingly, these neuroprotective effects of gintonin were blocked by LPAR1/3 antagonist, Ki16425. Overall, the present study shows that gintonin attenuates MPTP-induced neurotoxicity via multiple targets. Gintonin combats neuronal death, and acts as an anti-inflammatory and an anti-oxidant agent. It maintains BBB integrity. LPA receptors play a key role in gintonin-mediated anti-PD mechanisms. Finally, gintonin is a key agent for prevention and/or treatment of PD.